2009
DOI: 10.1007/s00128-009-9700-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Study of Leydig Cell Populations in Mice Exposed to Low Doses of Cadmium

Abstract: Leydig cell morphological changes were evaluated using morphometric and stereological methods in male mice exposed to low doses of cadmium. A possible reversibility of the changes after cadmium withdrawal was also considered. Nuclear morphological parameters and stereological densities of the Leydig cell population were lower in the cadmium-exposed groups than in the control. The withdrawal of cadmium did not lead to any significant recovery of the morphological parameters. Nevertheless, numerical density incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
(11 reference statements)
1
8
0
Order By: Relevance
“…Despite the reduction of Leydig cell cytoplasm in the GbE group compared with the control, these data are comparable with previous studies with rats [24,35,36]. The significant reduction of Leydig nuclear diameter that occurred in the cadmium treated group in accordance with the Leydig cell nuclear shrinkage and hyperchromatic images was reported by Blanco et al [37], who also found less circular Leydig cell nuclei. Ultrastructural observations, such as a diminished amount of endoplasmatic reticulum, mitochondria, and dense cytoplasmatic matrix, were found for Leydig cells.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the reduction of Leydig cell cytoplasm in the GbE group compared with the control, these data are comparable with previous studies with rats [24,35,36]. The significant reduction of Leydig nuclear diameter that occurred in the cadmium treated group in accordance with the Leydig cell nuclear shrinkage and hyperchromatic images was reported by Blanco et al [37], who also found less circular Leydig cell nuclei. Ultrastructural observations, such as a diminished amount of endoplasmatic reticulum, mitochondria, and dense cytoplasmatic matrix, were found for Leydig cells.…”
Section: Discussionsupporting
confidence: 92%
“…Hew et al [23] showed that a single low cadmium dose causes failure of spermiation in rats. Also, a substantial number of morphological and biochemical changes have been described for testes, such as germinal cell loss [17], Leydig cell degeneration [24], testicular mass and dimensions decreasing [25], and increased oxidative processes accompanied by a reduced proportion of antioxidant enzymes [13,14]. Hew et al [23] demonstrated that rats injected with cadmium chloride in a single dose of 1 mg/kg body weight did not show any significant change on the seminiferous tubules morphology, under the light microscope, 48 h after metal exposition.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by our research team have enabled us to confirm that exposure to compounds with a disruptor activity cause degenerative processes at a gonad level (BLaNCO et al, 2007;BLaNCO et al, 2009;PatrIgNaNI et al, 2014). We have also seen how BPa triggers important effects on ovaries and testicles, which could interfere with fertility (MOLINa et al, 2013;LOra et al, 2016), in addition to modifying other systems, such as the musculoskeletal system (gIMéNez et al, 2016).…”
Section: Resultsmentioning
confidence: 74%